The settlement option: friend or foe to human rights protection in Africa? (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT:The friendly settlement procedure has long existed in the Inter-American and the African human rights systems, yet over the past twenty years, it has become increasingly popular in the Inter-American system as a means to protect human rights and deliver remedies to victims. To date, over 150 settlements have been successfully negotiated at the level of the Inter-American Commission of Human Rights. The practice has differed, as has the impact of such settlements across the regions. Reports show that compliance with these agreements is generally better when compared to decisions on individual complaints. In contrast, the African system has rarely seen the amicable settlement option exercised successfully by the parties. This article outlines the advantages and disadvantages of the settlement option for the protection of human rights. The approach taken is an in-depth analysis of the procedure in both systems followed by a comparative analysis of the practice and its impact in the regions. In light of the practice in the Americas and Africa, the article interrogates and evaluates the overall utility of the settlement procedure and its potential for furthering human rights protection at the regional level, and in Africa specifically. This article finds that the settlement mechanism has numerous benefits for human rights protection if it is carried out according to established principles and clear criteria that seek to preserve the integrity of the procedure and the African human rights system more generally. TITRE ET RÉSUMÉ EN FRANCAIS:L’option de règlement: ami ou ennemi de la protection des droits de l’homme en Afrique?RÉSUMÉ:La procédure de règlement à l’amiable existe depuis longtemps dans les systèmes interaméricain et africain des droits de l’homme. Cependant, au cours des 20 dernières années, elle a de plus en plus été utilisée en tant que moyen de protection des droits de l’homme et des victimes dans le système interaméricain des droits de l’homme. À ce jour, plus de 150 règlements ont été négociés avec succès au niveau de la Commission interaméricaine des droits de l’homme. La pratique et l’impact de tels règlements à travers les régions diffèrent. Les rapports montrent que le respect de ces accords est généralement meilleur que celui des décisions relatives à des plaintes individuelles. En revanche, le système africain a rarement vu l’option de règlement à l’amiable être utilisée avec succès par les parties. Cet article décrit les avantages et les inconvénients de l’option de règlement pour la protection des droits de l’homme. L’approche adoptée consiste en une analyse approfondie de la procédure dans les deux systèmes, suivie d’une analyse comparative de la pratique et de son impact dans les systèmes régionaux. À la lumière de la pratique dans les Amériques et en Afrique, l’article examine et évalue l’utilité globale de la procédure de règlement et son potentiel pour renforcer la protection des droits de l’homme au niveau régional, et plus particulièrement en Afrique. L’article conclut que le mécanisme de règlement présente de nombreux avantages pour la protection des droits de l’homme s’il est mis en œuvre conformément à des principes établis et à des critères clairs visant à préserver l’intégrité de la procédure et du système africain des droits de l’homme plus généralement.
Keywords: African human rights systems; amicable/friendly settlement; human rights protection; inter-America Commission of Human Rights; African Commission on Human and Peoples’ Rights